(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This article attempts to describe the sexual and reproductive experiences of working women in Argentina, seeking a nexus in the tense maternity- working woman relationship that fundamentally characterizes the period 1900-1940. The main objective of the writing is to analyze the ways in which society regulated the female duty, naturalizing the motherhood that was endorsed by the scientific and cultural mandates of the time. We observe this through a bibliographic review that allows to give some visibility to the subject, both by the research strategies used, and by the theoretical analyses carried out. In short, we will start from devising the female-mother binomial as a social construct that crossed beliefs prevented the full enjoy of their civil, social and political rights.